Assessment of Genetic Diversity in Greengram (Vigna radiata L.) Using Metroglyph Analysis - , Sanagavarapu Sai Rajasree, Gabriel M. Lal (Archives of Current Research International, 2024)
Pulses like greengram are essential for sustainable agriculture and global food security due to their high protein, complex carbohydrates, fiber, vitamins, and minerals. However, their genetic diversity is underexplored, with existing studies mainly focusing on conventional methods. This study aims to estimate the variability parameters for 16 quantitative characters of greengram to classify the genotypes using Metroglyph analysis and assess genetic divergence to identify divergent parents for future hybridization programs using 45 greengram genotypes using Randomized Block Design replicated thrice. Among 45 genotypes of greengram on the basis of mean performance MGG-351(12.959) followed by MGG-347(43.16 q/ha), VBN -2 (41.12 q/ha), GM-3(40.8 q/ha) and MGG-385(39.8 q/ha) were found superior for grain yield. High GCV and PCV is recorded for Harvest Index and Number of primary branches. High heritability coupled with genetic advance as percent of mean are recorded for number of primary branches, harvest index (%), number of seeds per pod, biological yield per plant, seed index, number of pods per plant, number of clusters per plant. On the basis of Metroglyph analysis, the total index score was varied from 24 (SHAKTI) to 38 (SIKHA) with a mean of 31.84. Among the 45 germplasm lines, the genotypes GM-3, MGG-385, SML-1663 and MGG-371were observed as high yielder and identified for higher index score. Scatter diagram plotted with Plant Height and Harvest Index has revealed that 5 clusters could be distinguished on the basis of morphological variation. Cluster -1 was represented by 24 genotypes, Cluster -2 was represented by 10 genotypes, Cluster-3 was represented by 7 genotypes, Cluster-4 was represented by 3 genotype, Cluster -5 was represented by 1 genotype. From those complexes, the germplasm lines, SIKHA and MGG-371 recorded high index score and fell into different cluster, hence used as parents in hybridization for getting desirable transgressive segregants.